The Ability of Choreography Creative Thinking on Dance Performance - Triana, Dinny Devi (Department of Drama, Dance, and Musik (Sendratasik), Semarang State University, 2015)
This research aimed to measure the ability of creative thinking of dance students who became choreographer in Education University, in which their final project was creating a dance or dance creation. The method used for this research was correlative study, it was used to give a clear description of the correlation between predictor variable (ability of creative thinking) and respond variable (assessment of dance performance). The sample was collected by using purposive sampling. Based on the result, it was found that rsum was 0.510, while rtable for respondent n = 17 with significant scale 0.05 was 0.482. This meant rsum was bigger than rtable, and that meant there was correlation between the ability of creative thinking and dance performance. Significant test showed that zero hypotheses was rejected, it meant that there was significant correlation between creative thinking and dance performance. The result was table 1.75; and t sum was 2.3. It showed that H0 was rejected and H1 was accepted. It could be concluded that there was positive correlation between creative thinking and dance performance. Based on the coefficient determinant of the research result, it was found that the ability of students creative thinking was 25.96 percent, Â meanwhile 74.04 percent Â was determined by other factors which influenced dance performance.Â